Analisis Faktor-Faktor yang Memengaruhi Frekuensi Permintaan Konsumen terhadap Muslim Friendly Hotel di Kabupaten Belitung - Anggraini, Lilik; Nurhalim, Asep; Irfany, Mohammad Iqbal (Penerbit Goodwood, 2022)
Purpose: to analyze the characteristics and factors that influence the frequency of consumer demand for Muslim friendly hotels in Belitung Regency. Method: Descriptive analysis and multiple linear regression analysis Result: Indicate that the characteristics of the respondents are dominated by women, married, age range 26 to 35 years, the last education is undergraduate, work as a private employee, length of work less than 5 years, monthly income in the range of Rp. 3,000,000 - Rp. 5,000 .000 and domiciled in Belitung. Factors of income, religiosity, service quality, and facilities have a positive and significant effect on the frequency of consumer demand in using Muslim-friendly hotel services